Entangling entanglement: a diffractive dialogue on HCI and musical interactions - Morrison,L; McPherson,A (ACM, 2024)
If, as several recent papers claim, we have entered a new wave of “Entanglement HCI,” then we are still at a liminal stage prior to consensus around which sources underpin this paradigm shift or how they might inform actionable approaches to design practice. Now is the time to interpret technosocial mediation from a range of disciplinary perspectives, rather than settling on a narrow canon of literature. To this end, our paper enacts a diffractive dialogue between researchers from different disciplines, focusing on digital musical instruments to examine how technical knowledge from design and engineering can be read against the grain of critical theories from music, media, and cultural studies. Drawing on two object lessons—keyboards and step sequencers, plus their remediations inrecent musical interaction research—we highlight interdependencies of theory, design, and practice, and we show how the idea of entanglement is itself entangled in a cross-disciplinary web.